Paid domestic work and the struggles of care workers in Latin America. (July 2018) - Blofield, Merike; Jokela, Merita
About 30% of households are intimately involved in paid domestic work in Latin America, either as employers or as workers. Paid domestic workers overwhelmingly are female, from racial and ethnic minorities, and earn low wages. Labour codes have historically accorded them fewer rights and protections. Domestic workers have organized to demand equal rights, and recently, this organizing has begun to pay off. This article discusses the dynamics of paid domestic work through the themes of commodification and changes in government policies. Through a comparison of post-millennium Brazil, Uruguay, Mexico and Peru, the article compares the working conditions and struggles of domestic workers and highlights the factors that explain different outcomes in terms of labour rights and protections across these countries. It is argued that stronger rights and protections were made possible by the interactive effects of domestic workers organizing, more sympathetic left-wing governments, and the watershed ILO 2011 Convention on Domestic Workers.